Characteristics and outcome of patients with second primary lung cancer - Reinmuth, Niels; Stumpf, Andreas; Stumpf, Patrick; Muley, Thomas; Kobinger, Sonja; Hoffmann, Hans; Herth, Felix; Schnabel, Philipp Albert; Warth, Arne; Bischoff, Helge; Thomas, Michael (The European respiratory journal, 2013)
Patients with lung cancer are at risk of developing a second primary lung cancer (SPLC). However, the characteristics of patients at risk remain largely speculative. We reviewed 2816 lung cancer patients from our institution for the occurrence of SPLC. Any SPLC was categorised as synchronous when diagnosed within 2 years of the first primary lung cancer (FPLC) and after direct histological comparison of both tumours. All other SPLCs were considered as metachronous. 139 patients developed a second malignancy including 69 nonsmall cell lung cancer (NSCLC) and 9 small cell lung cancer. The median interval for diagnosis of metachronous SPLC (n=59) after FPLC occurrence was 72 months. SPLC detected within 5 years of FPLC diagnosis had a more favourable stage distribution (p=0.02). After diagnosis of SPLC, patients had a superior median overall survival compared to controls (57.7 versus 18.1 months; p<0.0001). Interestingly, comparing only stage IV NSCLC patients, a history of FPLC was also associated with a favourable survival (median 27.4 versus 8.97 months; p=0.007). In summary, previous lung cancer treatment does not lead to impaired prognosis after diagnosis of SPLC. Improved surveillance programmes beyond 5 years after FPLC treatment may result in more favourable disease stages for detected SPLC. Tweetable abstract ERSpublications click to tweetPrevious lung cancer treatment does not lead to impaired prognosis after diagnosis of secondary primary lung cancer http://ow.ly/oW5h6